How to Achieve Your Dreams - Pinkoon, Damrong (2015)
People can have a dream, but only some of them can make their dream come true. In 30 stories, you will learn how successful people can channel thei ability and endeavor to make things happen. They believe in the energy of life. If you never give up, your dream will come true some day. Never stop thinking because positive thoughts will change your life. Don’t lose your dream, because it is your dream that differentiates you from others. Never stop trying because the things you attempt in life will never hurt anybody. Don’t be weak because weakness will quickly destroy your heart. Never give up what you believe in, because to give up will make you a loser.